Kinetic and CFD Modeling of Exhaust Gas Reforming of Natural Gas in a Catalytic Fixed‐Bed Reactor for Spark Ignition Engines - Abdulwahid, Arman; Hagos, F. Y.; Abdul Adam, Abdullah; Abd Rashid, Abd Aziz; R., Mamat; Cheng, C. K.; Vo, Dai-Viet N. (Wiley, 2020)
Fuel reforming is an attractive method for performance enhancement of internal combustion engines fueled by natural gas, since the syngas can be generated inline from the reforming process. In this study, 1D and 2D steady‐state modeling of exhaust gas reforming of natural gas in a catalytic fixed‐bed reactor were conducted under different conditions. With increasing engine speed, methane conversion and hydrogen production increased. Similarly, increasing the fraction of recirculated exhaust gas resulted in higher consumption of methane and generation of H2 and CO. Steam addition enhanced methane conversion. However, when the amount of steam exceeded that of methane, less hydrogen was produced. Increasing the wall temperature increased the methane conversion and reduced the H2/CO ratio.